Pemanfaatan Ampas Kopi Menjadi Lilin Aroma Terapi di Pekon Ngarip Kecamatan Ulubelu - Rani Ismiarti Ergantara; Ahmad Sidiq; Gustamam Gustamam; Tri Kurniati; Hendrik Saputra; Rado Pratama; Yuliya Yuliya (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Ngarip Village, Ulubelu District, is one of the coffee-producing areas in Tanggamus Regency. Some residents process the harvested coffee into various micro, small and medium enterprises (MSME) products. This activity produces a byproduct in the form of coffee grounds. Coffee grounds have characteristics that allow them to be processed into products with utility and economic value. This community service activity aims to provide knowledge and skills to the Ngarip Village community on how to process coffee grounds into aromatherapy candles that are attractive, useful, and have the potential to be developed as a creative economy product. The implementation method includes literature studies, field observations, preparation of tools and materials, and socialization and training that includes material presentations, discussions, demonstrations, hands-on practice, and documentation. This training provides knowledge on the concept of 3R-based waste management and techniques for making aromatherapy candles using coffee grounds as an additional ingredient. The implementation results showed that participants were able to understand the process of making aromatherapy candles, from drying coffee grounds, melting wax, mixing ingredients, to the molding stage. Participants also gained knowledge about the benefits of aromatherapy candles for health, the environment, and their economic potential. This training can improve the community's ability to process waste into useful products, while also opening up sustainable home business opportunities. Overall, this activity has a positive impact on increasing public insight, creativity, and awareness regarding organic waste management, as well as encouraging innovations that support local economic independence.